EFEKTIFITAS BIRTH BALL DALAM MENURUNKAN NYERI PERSALINAN : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Labor pain is a uterine contraction and effacement caused by a decrease in the fetus during the delivery process. The fear and anxiety experienced by first-time mothers contribute to increased pain during labour. Birth ball is a natural pain relief method to help mothers reduce pain during labor. Purpose: The purpose of this evidence-based report is to determine the effect of the birth ball method on the pain intensity of the first active phase of labor at the Rancaekek Health Center. Method: The journal search method uses keywords, Boolean Operators and E-data based and is obtained from several articles that are found according to the inclusion and exclusion criteria then critically reviewed. Result: The birth ball was then applied to mothers giving birth in the first stage and the result was that the intervention was better compared to those who did not use the birth ball. Conclusion: The birth ball method was found to reduce the intensity of labor pain during the first active phase, according to the findings. It is hoped that health workers will use the Birth Ball to overcome the problem of pain in childbirth as an easy and cheap alternative that can be found by the community.